Perlindungan Pemilik Rahasia Dagang Dalam Perjanjian Waralaba - Anik Tri Haryani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2018)
Tight business competition requires creativity for entrepreneurs to stay competitive by seeking new breakthroughs in developing their businesses. Many franchise models are chosen to develop businesses. One of the criteria for franchising is the Intellectual Property Rights that have been registered including trade secrets. The purpose of this study is to examine the legal protection of trade secret owners in a franchise agreement, and legal consequences if there is a violation of trade secrets in the franchise agreement. The method used in this study is juridical normative with a law approach and conceptual approach. The results of the research show that the protection of trade secrets in the franchise agreement can be done by making an agreement which contains a confidential information, non disclosure agreement clause, a non compete agreement as well as a non solicitation agreement clause. Legal consequences in the event of a violation of trade secrets in the franchise agreement can be prosecuted civilly by paying compensation through a lawsuit to court or can be resolved through arbitration or alternative dispute resolution. In addition, it can also be prosecuted according to Article 17 paragraph (1) of Law Number 30 of 2000 concerning Trade Secrets with the penalty of imprisonment of a maximum of two years and a maximum fine of three hundred million rupiah.